Coronary microvascular remodelling in low oxygen microenvironment: Role of cilnidipine, a dual L/N type calcium channel blocker - Shrilaxmi Bagali; Akram Naikwadi; Kusal K Das (Wolters Kluwer Medknow Publications, 2020)
Background: People exposed to chronic sustained hypoxia (COPD) ultimately succumb to cardiovascular diseases. The heart is an obligate aerobic organ that requires a continuous supply of oxygen for its normal functions. Hence the structural and functional integrity of coronary microvasculature is very crucial for the normal functioning of the myocardium. Aims and Objectives: To assess the coronary microvascular remodelling in chronic sustained hypoxia exposure and its association with hypoxia signalling molecules. To study the role of cilnidipine, a unique calcium channel blocker (CCB) with dual L/N type calcium channel blocking actions with a documented cardioprotective role on chronic hypoxia-induced coronary microvascular remodelling. Methodology: 24 Wistar strain albino rats were randomly allocated into one of the four groups as follows - group 1, Control, (Normoxia, 21% O2); group 2, Chronic Hypoxia (CH) (10% O2, 90% N); group 3, Normoxia (21% O2) + Cilnidipine (Cil); group 4, Chronic Hypoxia (10% O2, 90% N) + Cilnidipine (CH+Cil). The intervention period was 21 days. Coronary microvascular remodelling was assessed by histopathological examination of the intramyocardial coronary artery. Normalised wall index (NWI) which is an indicator of arterial remodelling was calculated using histological images of coronary microvasculature using ImageJ software (https://imagej.nih.gov/ij/). Hypoxia signalling molecules like vascular endothelial growth factor (VEGF), endothelial nitric oxide synthase (NOS3), nitric oxide (NO) were estimated in the serum and their correlation with NWI was determined. Results and Conclusion: Histopathological examination of intramyocardial coronary artery demonstrated moderate arteriosclerosis and congestion on CH exposure. NWI was significantly increased indicating an overall increase in wall thickness. NWI and VEGF and eNOS were positively correlated. Cilnidipine treatment ameliorated the chronic hypoxia-induced coronary microvascular remodelling. Hence chronic hypoxia-induced coronary microvascular remodelling may be an early subclinical culprit in the pathogenesis of CVDs in patients exposed to hypoxia. The present study also reiterates the cardioprotective role of cilnidipine while opening new avenues for its role in coronary microvasculature in chronic hypoxia exposure.